Laki-Laki Usia 60 Tahun Dengan Snake Bite : Laporan Kasus60 Year Old Man With Snake Bite: Case Report - Athif Naufal; Yudi Eko Prasetyo (PT. Hasba Edukasi Mandiri, 2025)
Snake bite cases are one of the global public health problems, especially in tropical countries such as Indonesia. Snake bites can cause local and systemic symptoms such as redness, swelling, pain, hypotension, difficulty breathing and even death. In this case report, a 60-year-old male patient came to the Emergency Room of Ir. Soekarno Sukoharjo Hospital with complaints of right leg pain due to snake bites since 5 hours before entering the hospital. Complaints were accompanied by bluish swelling, heat, and numbness in the leg area after being bitten by a black snake in the garden. The patient had vomited 2 times. On physical examination, compos mentis consciousness was found (GCS E4V5M6), no shortness of breath. Blood pressure 174/80 mmHg, pulse rate 67 times per minute, respiratory rate 20 times per minute, axillary temperature 36o C. Normal geralis status. Local status showed vulnus morsum, bluish swelling in the right leg. There was tenderness. The patient received ATS injection treatment, 1 vial of anti-snake venom (ABU) in RL 500mg infusion, 30mg Ketorolac, 1gr ampicillin and ondansetron (iv).